Daging dan Ritual Adat: Kajian Teks 1 Korintus 8:1-13 - Surya, Agus (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2023)
The issue of eating meat offered to idols from time to time has not been completely discussed. There are still problems and conflicts among Christians regarding eating meat offered to idols or traditional rituals. This study aims to analyze the problem of eating meat and traditional rituals in terms of the text of 1 Corinthians 8:1-13. The literature method is the approach used in this study. The results revealed that meat that had been offered as a traditional ritual offering from the light of 1 Corinthians 8:1-13 confirmed that wise living and conscience were key to action. Eating meat used in traditional rituals should consider aspects of conscience and be an example in life, so as to avoid stumbling blocks.